1981
DOI: 10.1111/j.1440-1681.1981.tb00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Blood Pressure in a Working Population

Abstract: 1. The association between alcohol consumption and blood pressure was studied in 491 Government employees. The men, aged 21-45 years, volunteered to complete a health questionnaire and submitted to standardized measurements of blood pressure, heart rate and body size. 2. Average weekly alcohol consumption correlated with systolic pressure (R = 0.18, P less than 0.001) but not with diastolic pressure. Systolic pressure increased progressively with increasing alcohol consumption with no obvious threshold effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

1983
1983
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
1
2
0
1
Order By: Relevance
“…This J shaped curve has been reported by several groups where the sample size of the population was large enough to detect it [10,17,18,19]. Some smaller studies from Australia and Tasmania could only show a linear relationship [9,13,14]. There are several possible explanations for the slightly higher blood pressure levels in tee-totallers; possibly some heavy drinkers denied their alcohol consumption completely or they had given up drinking at the time of the epidemiological survey due to intercurrent illness.…”
Section: The J Shaped Curvesupporting
confidence: 53%
See 1 more Smart Citation
“…This J shaped curve has been reported by several groups where the sample size of the population was large enough to detect it [10,17,18,19]. Some smaller studies from Australia and Tasmania could only show a linear relationship [9,13,14]. There are several possible explanations for the slightly higher blood pressure levels in tee-totallers; possibly some heavy drinkers denied their alcohol consumption completely or they had given up drinking at the time of the epidemiological survey due to intercurrent illness.…”
Section: The J Shaped Curvesupporting
confidence: 53%
“…In 1977 a major analysis was reported from a survey of nearly 84,000 people in the Kaiser Permanente Health Examination Programme [ 10]. This is the largest epidemiological study to show a relationship between alcohol consumption and blood pressure and has since been confirmed by many other studies [11][12][13][14][15]. Klatsky et al [10] demonstrated that both systolic and diastolic pressure were related to alcohol consumption and the effect was independent of differences in age, sex, ethnic group, body mass index, cigarette consumption, salt preference [16], coffee intake or social class.…”
Section: Early Studiesmentioning
confidence: 92%
“…Considerable research has suggested a relationship between alcohol intake and blood pressure levels, within both employed populations (1)(2)(3)(4)(5) and community samples (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Most of this work has shown that this relationship exists independently of other risk factors such as obesity, smoking, and age, although one recent study, a health survey of Canada, (16), did not obtain this finding.…”
mentioning
confidence: 99%
“…Um outro fator que poderia ter alguma relevância para explicar as variações de pressão é a ingestão freqüente de bebida alcoólica, cuja conexão com níveis mais elevados de pressão já foi apontada 2,23 , inclusive em Volta Redonda 15 . Já que a maioria das variações significativas ocorreu na pressão diastólica, poderia ser lembrado ainda o papel desempenhado pela obesidade 3,12,23 .…”
Section: Discussionunclassified